Biomechanical properties of celiotomy wounds closed with tape and cyanoacrylate versus intradermal sutures. Issue 8 (10th October 2018) - Kitshoff, Adriaan M.; Louwagie, Johanna; Or, Matan; Devriendt, Nausikaa; Dehuisser, Virginie; Koenraadt, Annika; Vandenabeele, Sophie; Sys, Stanislas U.; de Rooster, Hilde
Abstract: Objective: To compare cutaneous wound closure with mesh and 2‐octyl cyanoacrylate (MOC) vs an intradermal suture pattern (ISP) in terms of time of application and biomechanical properties. Sample population: Experimental study with 12 female beagle dogs. Methods: A skin incision was created from the xiphoid to the pubis as part of an ovariohysterectomy; the linea alba and subcutaneous tissue were closed routinely. Half of the skin incision was closed with MOC, and the other half was closed with an ISP. Tissue samples were collected from both sections at days 14 and 28 and tested for ultimate strength and stiffness. Results: Closure with MOC (72.8 ± 14.0 s) was faster than with an ISP (398.4 ± 36.4 s; P = .001). The ultimate load and stiffness increased with time for MOC ( P = .005 and P = .005, respectively) and ISP ( P < .001 and P < .001, respectively). On day 14, ultimate load and stiffness were greater in wounds closed with MOC compared with ISP ( P = .014 and P = .02, respectively). No difference between groups was detected at day 28. Conclusion: Cutaneous wound closure with MOC was faster and resulted in superior strength at 14 days compared with closure with an ISP in this healthy population. Clinical significance: Mesh and 2‐octyl cyanoacrylate offers an attractive alternative to ISP for skin closure after celiotomy in dogs, especially if surgical/anesthesia time is a concern.